Development of Cytolytic Iridium-Complexed Octaarginine Peptide Albumin Nanomedicine for Hepatocellular Carcinoma Treatment - Sun X; Wang D; Chang S; Yin L; Zhang H; Ji S; Fei H; Jin Y (International Journal of Nanomedicine)
Xingwei Sun,1,* Di Wang,1,* Shiwei Chang,2,* Liang Yin,1 Hao Zhang,1 Shuangshuang Ji,2 Hao Fei,2 Yong Jin1 1Department of Interventional Radiology, The Second Affiliated Hospital of Soochow University, Suzhou, 215004, People’s Republic of China; 2Nanobiomedicine Division, Suzhou Institute of Nano-Tech and Nano-Bionics, Chinese Academy of Sciences, Suzhou, 215123, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yong Jin, Email jinyong@suda.edu.cn Hao Fei, Email hfei2008@sinano.ac.cnObjective: Hepatocellular carcinoma is one of the most challenging malignancies and has high incidence and mortality rates worldwide. Digital subtraction angiography (DSA)-guided hepatic arterial infusion of the standard chemotherapeutic agent oxaliplatin (OXA) has the advantages of both precision and efficacy, making it an important therapeutic strategy for advanced-stage liver cancer. However, patients receiving this treatment still face severe systemic toxicity and poor tolerability of oxaliplatin.Methods: In this study, we compared oxaliplatin with novel albumin-formulated oncolytic peptide nanoparticles, Ir-cR8 (abbreviated as iPep), in the treatment of orthotopic liver cancer in a mouse model by intravenous injection and in a rabbit model via DSA-guided hepatic arterial infusion.Results: The results showed that intravenous Ir-cR8-BSA-NPs had enhanced inhibitory effects to the growth of H22 ectopic liver tumors in mice and also with reduced toxicity in animals compared to OXA treatment. Specifically, Ir-cR8-BSA-NPs-treated mice showed approximately 92% tumor growth inhibition compared to approximately 88% for OXA. In the rabbit VX2 ectopic hepatocellular carcinoma model, Ir-cR8-BSA-NPs demonstrated significantly stronger inhibition (P< 0.01) of tumor size compared to OXA, as assessed by PET/CT imaging, with SUV values decreasing from 5.15± 0.46 to 2.52± 0.57, compared to OXA-treated group, which decreased from 5.44± 0.43 to 3.90± 0.24. Furthermore, Ir-cR8- BSA-NPs significantly improved stability by albumin encapsulation and reduced hemolytic toxicity (P< 0.001), resulting in improved therapeutic efficacy.Conclusion: This study demonstrated the combined advantages of a novel membrane-active oncolytic peptide nanomedicine and precise drug delivery enabled by arterial infusion technology for the interventional treatment of liver cancer.Keywords: interventional treatment, hepatocellular carcinoma, Ir-cR8-BSA-NP, microspheres, nanomedicine